Multicopter Attitude Control through NMPC Design with Guaranteed Stability. Issue 2 (2020) - Nguyen, Ngoc Thinh; Prodan, Ionela; Lefèvre, Laurent
Abstract: This paper presents an original NMPC (Nonlinear Model Predictive Control) design with guaranteed stability for the attitude set-point angle tracking of multicopters. The design is an extension of our previous work on stabilizing the NMPC scheme for "computed-torque like" systems by using terminal invariant set constructed under the CTC (Computed-Torque Control) controller. The novelty resides in the complexity reduction for the design process which is done by reducing the dependence of the required elements (e.g., the terminal region's radius, the Lipschitz constant) on the desired angle set-points which change fast and are not known in advance. The contributions are validated in simulation over a quadcopter model.